2018
DOI: 10.1177/1753944718756604
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ambulation after vascular access closure device

Abstract: Background:Patients who are candidates to receive an Angioseal® (St. Jude Medical) device for arteriotomy closure are allowed to ambulate 20 min after the deployment of the device. More frequently, however, patients are kept on bed rest for several hours following Angioseal® deployment. The purpose of this study was to prospectively assess patients when ambulating 20 min after Angioseal® deployment instead of prolonged best rest of 2-3 h. Methods: Patients undergoing angiography from the common femoral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“… 1 , 2 , 4 , 5 Increased patient satisfaction, comfort as well as accelerated ambulation have also been reported. 6 , 7 Some studies have shown that certain types of VCDs are 95–100% effective in achieving hemostasis with minimal complications. 3 , 8 10 In addition, the use of ultrasound-guidance of femoral artery access has increased the safety and effectiveness of the VCDs.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 4 , 5 Increased patient satisfaction, comfort as well as accelerated ambulation have also been reported. 6 , 7 Some studies have shown that certain types of VCDs are 95–100% effective in achieving hemostasis with minimal complications. 3 , 8 10 In addition, the use of ultrasound-guidance of femoral artery access has increased the safety and effectiveness of the VCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Some institutes have percutaneous closure devices too. 7 We should be careful to prevent groin hematoma. The limb is immobilized with a sandbag kept on top of the dressing gauze.…”
Section: Post-proceduresmentioning
confidence: 99%
“…Arterial closure devices, following arterial puncture for endovascular procedures, are frequently used because of their ability to secure reliable haemostasis allowing for early mobilisation and shorter hospital stays. 1-4 The Angio-Seal device (Terumo, Europe NV) is one of the most commonly used devices for closure of the femoral artery and incorporates a collagen plug and footplate to seal the puncture site. 2,4…”
Section: Introductionmentioning
confidence: 99%